THE INFLUENCE OF LEARNING PREPARATION AND LEARNING STYLE INTERESTS TOWARD MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VII - Zaenab Safarinah; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
This study is based on students' low learning outcomes, low learning preparation, and lack of optimization of learning style math learning causes less effective mathematics study. This research aims to determine whether there is influence toward math learning outcomes among students who have a high or low learning preparation and learning style visual, auditorial, or kinesthetic in the students Class VII of State Junior High School (SMP Negeri) 1 Banjarmangu Banjarnegara Regency in Even Semester Academic Year 2017/2018. This research population was the students of class VII SMP Negeri 1 Banjarmangu Banjarnegara Regency in even semester academic year 2017/2018, which consists of 7 classes. With Random Sampling Technique to the class and obtained class VII G as a class of research sample and class VII F as a class of research trial. Data collection techniques used a questionnaire form and test. A multiple-choice test is a matter of learning mathematics outcomes in the form of a questionnaire for the learning preparation and learning style. Instrument test: validity test, different power tests, and reliability test. Test requirement analysis includes a test of normality and tests its homogeneity. Data analysis used a two-way analysis of variance 2×3 with the different cells and Tukey's HSD test. This research indicates a positive and significant influence of learning preparation and learning styles in the mathematics learning outcomes in students class VII SMP Negeri 1 Banjarmangu Banjarnegara Regency in even semester academic year 2017/2018.  It is showed by  and  so that  with a significance level of 5%.